Cost-effectiveness analysis of tislelizumab plus chemotherapy as the first-line treatment for advanced or metastatic esophageal squamous cell carcinoma in China - Liu, Yanhong; Shao, Rong (Frontiers in Pharmacology, 2024)
Introduction: First-line tislelizumab plus chemotherapy has shown clinical benefits for patients with advanced or metastatic oesophageal squamous cell carcinoma (OSCC) in China, while its economic burden is unknown. This study aimed to evaluate the cost-effectiveness of tislelizumab plus chemotherapy from the perspective of the Chinese healthcare system.We constructed a partitioned survival model to compare the cost-effectiveness of tislelizumab plus chemotherapy with chemotherapy in patients with advanced OSCC. Patient characteristics and clinical outcomes were extracted from RATIONALE-306. Costs, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratios (ICER) were selected as study ooutcomes.Sensitivity analysis and subgroup analysis were conducted to test the stability of results.Results: Tislelizumab plus chemotherapy provided additional 0.48 QALYs with incremental cost of 16,587.2 than chemotherapy, of which the ICER was 34699.72 per QALY. When the willingness-to-pay threshold was set as 37,260, novel therapy had a probability of 77% to be cost-effective. Our base-case analysis results were sensitive to utilities of progression-free survival and progression disease. Our subgroup analysis showed that novel therapy was associated with cost-effectiveness in patients with high expression of PD-L1.Tislelizumab plus chemotherapy was likely to be cost-effective compared with chemotherapy in the first-line therapy of advanced OSCC from the perspective of Chinese healthcare system. Our findings can provide clinicians and decision-makers with evidence of the cost-effectiveness of tislelizumab.